Systematic Review: The Association and Impact of Financial Conflicts of Interest in Basic Science Research - Bennett, Charles L. (2010)
BACKGROUND: No prior study has evaluated financial relationships of investigators with pharmaceutical manufacturers for basic science. An example of the importance and impact of such relationships is in the evaluation of erythropoietin receptors’(EpoRs) effects on cancer cell lines, since studies have reported increased mortality when cancer patients receive erythropoiesis stimulating agents (ESAs). PURPOSE: To assess the disclosed association that exist between pharmaceutical industry support and EpoRs effects on solid cancer cell lines. DATA SOURCES: MEDLINE and EMBASE (1988- July 2008) and two EpoR conferences sponsored by the National Institutes of Health. STUDY SELECTION: All publications investigating EpoRs that met inclusion criteria were identified and included. DATA EXTRACTION: Data were extracted on detection of EpoRs, presence of erythropoietin-induced signaling events, presence of erythropoietin-induced changes in cellular function, nature of qualitative conclusions, and sources of funding for all 74 studies. DATA SYNTHESIS: In comparison to studies of academic investigators with no disclosed funding support from ESA manufacturers (n=64), the studies from academic investigators with funding support from ESA manufacturers (n= 7) and the laboratories directed by investigators employed by ESA manufacturers (n=3) were both less likely to identify: EpoR presence on solid tumor cells; erythropoietin-induced signaling events; erythropoietin-induced changes in cellular function; and less likely to conclude that their research had identified potentially harmful effects of erythropoietin on cancer cells. Additionally, presentations from industry-based investigator teams at NIH conferences were less likely to report EpoRs on cancer cell lines, downstream effects of erythropoietin, and cell proliferation and migration effects following EpoR administration. CONCLUSION: Financial conflicts of interest impact the outcomes and presentation of basic science research data as well as publications.